Inside or outside detecting the cellular location of bacterial pathogens - Edwards, R A (BioTechniques, 2001)
Salmonella are intracellular pathogens that infect and multiply inside macrophages. Although Salmonella are some of the best-studied pathogens, it is difficult to determine quickly and reliably whether the bacteria are intracellular or extracellular. We have developed a novel method using differential fluorescence of two fluorescent proteins to determine the cellular location of pathogenic bacteria in macrophage infection assays. Using the differential expression of two unique fluorescent proteins that are expressed under specific conditions, we have developed a real-time assay for macrophage infections. The critical advantages of this system are that it does not alter the bacterial surface, it is not toxic to either the bacteria or the host cell, and it may be used in real-time quantitative assays. This assay can be readily applied to any other model pathogenic systems such as Listeria, Mycobacteria, and Legionella in which intracellular gene expression has been characterized